2014
DOI: 10.1007/s00204-014-1332-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the toxicity of aluminum oxide nanorods with different aspect ratio

Abstract: Aluminum oxide nanoparticles are listed among 14 high-priority nanomaterials published by the Organization for Economic Co-operation and Development, but limited information is available on their potential hazards. In this study, we compared the toxicity of two different aluminum oxide nanorods (AlNRs) commercially available in vivo and in vitro. Considering aspect ratio, one was 6.2 ± 0.6 (long-AlNRs) and the other was 2.1 ± 0.4 (short-AlNRs). In mice, long-AlNRs induced longer and stronger inflammatory respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…Moreover, in the real‐time proliferation assay, which measures electrical impedance on the plate bottom, α‐ and γ‐AlONPs generally restored proliferation speed with time, but BEAS‐2B and H9C2 cells exposed to γ‐AlOHNPs (20 µg ml −1 ) did not proliferate until 48 h after exposure. Therefore, we suggest that BEAS‐2B cells exposed to γ‐AlOHNPs may induce the highest toxicity, although results from toxicity assessment tools used in this study conflicted (Park et al ., ). Furthermore, the MTT assay and ATP assay are used to assess effects on mitochondrial function, whereas the LDH assay evaluates membrane integrity.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, in the real‐time proliferation assay, which measures electrical impedance on the plate bottom, α‐ and γ‐AlONPs generally restored proliferation speed with time, but BEAS‐2B and H9C2 cells exposed to γ‐AlOHNPs (20 µg ml −1 ) did not proliferate until 48 h after exposure. Therefore, we suggest that BEAS‐2B cells exposed to γ‐AlOHNPs may induce the highest toxicity, although results from toxicity assessment tools used in this study conflicted (Park et al ., ). Furthermore, the MTT assay and ATP assay are used to assess effects on mitochondrial function, whereas the LDH assay evaluates membrane integrity.…”
Section: Discussionmentioning
confidence: 97%
“…S‐AlONPs were well dispersed (Figure A), whereas L‐AlONPs showed an aggregated appearance (Figure B). S‐ and L‐AlONPs had anisotropic shapes with different aspect ratios (length‐to‐diameter) of 2.1 ± 0.4, and 6.2 ± 0.6, respectively (Park, Lee, et al, ; Park, Kim, et al, ). The XRD patterns obtained from both S‐ and L‐AlONPs were primarily indexed to δ phase, although S‐AlONPs were δ phase with the I space group (PDF no.…”
Section: Resultsmentioning
confidence: 99%
“…S‐ and L‐AlONPs and AlCeONPs were purchased from Sigma‐Aldrich (catalog nos 718475, 544833 and 637866; St. Louis, MO, USA) and loaded in deionized water at a concentration of 1 mg ml −1 . As described previously (Park, Lee, et al, ; Park, Sim, et al, ; Park, Kim, et al, ), each sample was dispersed in a stable fashion by sonication twice for 10 minutes in a bath‐type sonicator (150 W, 40 kHz). The temperature of the sonicator was maintained below 30°C to prevent agglomeration between the particles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, NPs of a certain size range have recently emerged as an inhalable pollutant that can travel deeper into the lungs than microsized particles (El-Sherbiny, El-Baz, & Yacoub, 2015;Hoet et al, 2004). Some researchers also suggested that NPs can impair the defense mechanisms of the host and persist for a long time in the lungs owing to their unique properties (Braydich-Stolle et al, 2010;Chang, Fu, Zhang, Tang, & Wang, 2014;Park et al, 2015;Tkach et al, 2011). In this study, we aimed to identify the properties that determine pulmonary accumulation and the subsequent toxicity of aluminumbased NPs (Al-NPs).…”
mentioning
confidence: 99%